Volatile organic compound profiling as a potential biomarker in irritable bowel syndrome: A feasibility study - Van Malderen, Kathleen; Hanning, Nikita; Lambrechts, Helen; Haverhals, Tine; Van Marcke, Silke; Ceuleers, Hannah; De Man, Joris G.; De Winter, Benedicte Y.; Lamote, Kevin; De Schepper, Heiko U. (Frontiers in Medicine, 2022)
Background: Irritable bowel syndrome (IBS) is a chronic gastrointestinal disorder for which no diagnostic tools are currently available. Patients are diagnosed using the Rome IV criteria and subtyped into a diarrhea, constipation, or mixed phenotype based on their dominant stool pattern. A recent development in the biomarker area is the analysis of volatile organic compounds (VOCs). The aim of this study was to evaluate the potential of VOCs as diagnostic and phenotypic biomarkers for IBS in breath and fecal samples. Methods: Breath and fecal samples from IBS patients and healthy asymptomatic controls (HC) were analyzed with multicapillary column/ion mobility spectrometry (MCC/IMS) and classification models were created based upon VOCs and clinical characteristics. Discussion: IBS patients were differentiated from HC by means of volatile profiling in both breath and fecal samples with AUCs of respectively 0.62 and 0.80. Patient subtypes could also be differentiated from each other with AUCs ranging between 0.65 and 0.78. Furthermore, VOC models could differentiate IBS patients based on clinical characteristics like psychological comorbidities and microbiota-influencing therapies. Conclusion: This study is the first to demonstrate the use of VOC profiling with the help of MCC/IMS to differentiate IBS patients. Furthermore, the importance of clinical characteristics beside the dominant stool pattern in the differentiation of IBS patients was emphasized.